The Effect of Initial Anti-tuberculosis Drug Therapy on Transminase Enzymes - Muhammad Gugun, Adang; Suryanto, Suryanto; Ranti Ayuningtyas, Dyah Nova (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Tuberculosis is still a health problem in the world. TB treatment is carried out in 2 phases, namely early and advanced. This study aims to determine changes in serum transaminase enzyme levels (SGOT and SGPT) in pulmonary TB patients before and after initial drug administration. This study was observational with a cohort study design study. Observations were conducted in tuberculosis patients who received initial ATD therapy for 2 months for SGOT and SGPT enzyme levels before and after treatment. The subject of the study was a new case of a pulmonary TB patient aged ?16 years. Subjects received initial therapy in the form of isoniazid, rifampicin, pyrazinamide, and ethambutol. Recruitment of subjects through successive sampling methods with informed consent. Using a spectrophotometer, SGOT and SGPT enzyme tests were performed on the median blood serum cubital vein. Data analysis using the Wilcoxon Test. The study involved 19 subjects (10 men and 9 women) aged 16-65 years. Before ATD, the mean SGOT was 22.84 IU/L, and SGPT was 21.37 IU/L. After ATD, SGOT increased to 58.63 IU/L (p = 0.023), and SGPT to 80.84 IU/L (p = 0.007). Of the 19 subjects, 8 experienced a significant increase in SGOT and 5 SGPT. Five cases showed an increase in SGPT in line with SGOT, and 3 cases showed an increase in SGOT without SGPT. One case saw an increase in SGOT and SGPT of more than 5 times the reference value. This study confirms an increase in transaminase enzymes during initial therapy with first-line ATD.